ANALISIS KEBIJAKAN TENTANG SERTIFIKASI PENDIDIK GURU DAN DOSEN - Amruzziyad; Siti Nasroh; Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Teacher and lecturer certification is one of the important policies in improving the quality of education in Indonesia. This policy aims to ensure that educators have adequate competence in accordance with national standards. This study analyzes teacher and lecturer certification policies with a focus on implementation, impact, and challenges faced. The research method used is a literature study by collecting data from various sources such as journals, government reports, and policy documents. The results of the study indicate that certification has had a positive impact on improving the welfare of teachers and lecturers, but there are still challenges in terms of equity, quality of implementation, and ongoing evaluation. Policy recommendations are proposed to improve the certification system to make it more effective and sustainable.